ETR 300 : Splatter Colour Decoration / Norani Mansor ... [et al.] - Mansor, Norani; Abd Karim, Nor Hafizah; Abd Rahim, Rahizatul Adawiah; Murat, Aslinda; Yasin, Ropizah (2000)
SPLATTER COLOUR DECORATION is a business that provides fabrics, wallpaper and services. This business is operating at No.13, Lengkok Cempaka 1, Persiaran Cempaka 08000,Bandar Amanjaya,Sungai Petani Kedah Darulaman. Splatter Colour Decoration provide many kinds of fabrics that can make curtain and cushion. All fabrics have high quality and sell at standard price. This business also gives services to select and make curtain and cushion cover. Customer has a lot of choice from many types of fabrics. At Splatter Colour Decoration, we also have imported and local fabrics with high quality. This business also offers to make curtain and cushion cover. There so many pattern and design are offer to the customers. The design very up to date and beautiful.